Sub-background radiation exposure at the LNGS underground laboratory: dosimetric characterization of the external and underground facilities - Ampollini, Marco; Anello, Pasqualino; Balata, Marco; Bortolin, Emanuela; Chiarelli, Federico; Chiti, Daniele; Chiti, Maurizio; De Angelis, Cinzia; D’Imperio, Giulia; Donghia, Raffaella; Esposito, Giuseppe; Ferella, Francesco; et al. (Frontiers in Physics, 2023)
Radiobiological studies conducted in Deep Underground Laboratories allow to improve the knowledge of the biological effects induced by ionizing radiation at low doses/dose rates. At the Gran Sasso National Laboratory of the Italian Institute of Nuclear Physics we can study the possible differences in behavior between parallel biological systems, one maintained in a Reference-Radiation Environment (RRE, external) and the other maintained in an extremely Low-Radiation Environment (LRE, underground), in the absence of pressure changes, the RRE and LRE laboratories being at the same altitude. For these investigations, it is mandatory to evaluate the dose rate values at RRE and LRE. The aim of this work is to provide a comprehensive dosimetric analysis for external and underground laboratories. Measurements of the different low Linear Energy Transfer (LET) components at RRE and LRE were performed using different detectors. Gamma dose rates were 31 nSv/h and 27 nSv/h at RRE and LRE respectively. The muon dose rate was 47 nSv/h at RRE and negligible at LRE (less than pGy/h). Dosimetric measurements were also carried out to characterize the devices used to modulate the gamma dose rate, namely a gamma source irradiator (to increase the dose rate by about 90 nSv/h) and shields (of iron at LRE and lead at RRE). Using the iron shield at LRE a dose reduction factor of about 20, compared to the RRE, was obtained for the low LET components; inside the lead shield at RRE the gamma component was negligible compared to the muonic component. Radon activity concentrations were approximately of 20 Bq/m3 at both LRE and RRE. The intrinsic contribution of radioactivity in the experimental set up was of 0.25 nGy/h, as evaluated with a GEANT4 simulation, using as input the measured activity concentrations. GEANT4 simulations were also performed to calculate the neutron dose rate at RRE, yielding a value of 1.4 nGy/h, much larger than that at LRE (which is less than pGy/h). In conclusion, RRE and LRE are currently characterized and equipped to perform radiobiological studies aimed at understanding the involvement of the different low LET components in determining the response of biological systems.